Microstructure of dental casting alloy Ni-Cr-Mo (Rodent) - Korneva, Anna; Orlicka, Izabela; Sztwiertnia, Krzysztof; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2014)
Microstructure of the dental alloy Ni-Cr-Mo (Rodent) after casting in the vacuum-pressure furnace has been examined. Chemical analysis by using energy dispersive spectroscopy as well as crystallographic orientations topography by using backscattered electron diffraction in the scanning electron microscope was carried out. It was found that after casting the microstructure consists of dendrites of solid-solution strengthened nickel–chromium matrix (γ phase). Inside the dendrites the precipitations of molybdenum silicides, eutectics γ–P and few particles of aluminum oxide were observed.Досліджено мікроструктуру стоматологічного сплаву Родент на основі Ni-Cr-Mo після лиття у вакуум-печі. За допомогою методу енергодисперсійної спектроскопії проведено хімічний аналіз, а за допомогою дифракції зворотньо відображених електронів в растровому електронному мікроскопі проведено топографію кристалографічної орієнтації. Встановлено, що після лиття мікроструктура містить дендрити твердого розчину, що зміцнюють нікель-хром матрицю (γ-фазу). Показано, що всередині дендритів спостерігаються виділення карбідів молібдену, евтектика γ-P і декілька частинок оксиду алюмінію.
Мікроструктура стоматологічного литого сплаву Родент на основі Ni-Cr-Mo
Keywords: microstructure; dental alloy; casting; мікроструктура; стоматологічний сплав; лиття